Issue and the Effect of Poor Drainage System in Urban Area Toward Flood Problem: A Case Study at Cheng, Malacca - Mat Supri, Nizar Asyraf; Adnan, Mohd Shalahuddin (Recent Trends in Civil Engineering and Built Environment, 2024)
Abstract: The problem of floods at this time has become a very worrying incident due to the various destruction and loss of property suffered by the victims in the community. Inadequate drainage capacity is one of many causes that lead to flooding in urban area. Therefore, the drainage network and drainage capacity are considered as an important and indispensable infrastructure for the city. Cheng district area has often faced flash floods in recent times. This research work will focus on identification of problems and causes related with flash floods. The main objective of this study is to identify current issue regarding flash floods problem that may be due to the performance of the existing drainage capacity. Due to inadequate size, lack of proper maintenance and tidal effect, the existing drains in most of the places are not accommodate with the increasing of flow during the rainy season. Therefore, the rainfall data will be study to identify the relationship between the data and current situation. In this study, Quantum Geographical Information System, QGIS will be utilized to produce hydrological mapping model that could be used to evaluate the flow discharge. To simulate the catchment chosen, Rational Method will be used for analyzing the existing drainage system. This case study work would be able to propose several solutions to avoid and reduce the issues by using the selected method plan. Keywords: Drainage, Flash Flood Problem, Hydrological Mapping Model, Quantum Geographical Information System QGIS